Pendampingan Pendeta sebagai Theopreneur dalam Meningkatkan Kesejahteraan Jemaat di HKI Resort Pulo Siborna, Kecamatan Panei - Rahul Sihombing (International Forum of Researchers and Lecturers, 2026)
The church has a strategic role not only in spiritual development, but also in the social and economic empowerment of the congregation. One relevant approach to address the challenges of congregational welfare is Theopreneurship, namely entrepreneurship based on Christian faith values. This study aims to determine how the form of pastor's mentoring as Theopreneur in improving the welfare of the congregation at HKI Resort Pulo Siborna, Panei District. The approach used is descriptive qualitative with data collection methods through interviews, observation, and documentation. The results of the study show that the pastor plays an active role as a facilitator, motivator, and spiritual guide in assisting the congregation in developing businesses based on faith values. The socio-economic development (PSE) program, which covers agriculture and animal husbandry, has successfully fostered an entrepreneurial spirit, togetherness, and the economic independence of the congregation. The pastor's mentoring as a Theopreneur has proven to be able to provide holistic services that emphasize not only the spiritual aspect but also the economic empowerment of the congregation. Thus, the pastor's mentoring as Theopreneurship has a positive contribution in improving the welfare of the congregation holistically, encompassing spiritual, social, and economic aspects. Therefore, Theopreneurship can be a model of contextual and sustainable church service in realizing the welfare of the congregation as a whole.